Estimating the Genuine Progress Indicator before and during the COVID pandemic in Australia. (August 2022) - Karatopouzis, Alexandros; Voinov, Alexey A.; Kubiszewski, Ida; Taghikhah, Firouzeh; Costanza, Robert; Kenny, Daniel
Highlights: During Australia's first nationwide lockdown, the GPI was less impacted than the GDP. More leisure time, less commuting and household work expenses, were reflected in the GPI. Alternative indicators like GPI can track uneconomic growth and guide policy makers. Microdata can improve accounting of GPI's subjective components, but more difficult to obtain during lockdown. Abstract: In the efforts to ensure the health of the Australian population during the COVID pandemic, social, economic, and environmental aspects of people's life were impacted. In addressing the pandemic risks, a number of governments prioritized people's health and well-being over GDP growth. The Genuine Progress Indicator (GPI) is used to account for factors that influence well-being. We used the GPI to assess the pandemic's impact on well-being and we examined our results in relation to the GDP. We estimated the GPI for the first 6 months of 2019 and the same period in 2020, during which the first stages of the COVID pandemic and the first nationwide lockdown in Australia took place. We examined two scenarios, in the first we found that in Q1 the GDP growth (1.4%) was accompanied by a significant GPI growth (5.3%), showing a positive relation to the GDP; but in Q2 the significant drop (-6.3%) in the GDP was not followed by the GPI, instead the GPI growth remained almost steady with even a relatively small increase (0.33%), indicating a negative relation to the GDP growth. Whereas in the second scenario, the GPI growths (7.12%) in Q1 and (-2.60%) Q2 were positively related to the GDP growths (4.6%) in Q1 and (−0.25%) Q2.We discuss the reasons for the divergence between the two indicators and one of the limitations of the GPI as a measure of well-being. Lastly, we discuss the behavioural and policy lessons of the lockdown and their relevance to what is proposed by degrowth economists.